BUSINESS MODEL CANVAS PADA USAHA PENJUALAN BOX BATERAI MOTOR LISTRIK - Kukuh Priyo Pramono; Syukri M. Nur (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
In this era of rapid technological growth, especially in the transport sector, the development of electric vehicle in Indonesia has been a major focus since 2012. Government support through various regulations such as Perpres, Permenhub, and Permen ESDM, as well as changes to the taxation system for electric vehicles, create a legal foundation for the use and production of electric vehicles. As the adoption of electric vehicles in Indonesia, particularly electric motorbikes, increases, the need for reliable batteries becomes increasingly important. However, the adoption of electric vehicles is faced with several obstacles, such as the difficulty of finding Public Electric Vehicle Charging Stations (SPKLU) and Public Electric Vehicle Battery Swapping Stations (SPBKLU) and the high price of electric vehicles. The focus of this research is to understand the relationship between the number of stations and community mobility. In an effort to find a solution, this research uses Business Model Canvas (BMC) to describe and evaluate the business model of battery box sales and installation services for electric motorbikes. The BMC results show that this business focuses on electric motorbike owners in areas that do not have SPBKLU, offering a solution to extend the mileage of electric motorbikes.